(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The BRICS countries, Brazil, Russia, India, China, and South Africa, have emerged as key players in the global economy over the past two decades. This group of nations represents over 40% of the world’s population and accounts for a significant portion of global GDP. The rise of the BRICS countries has challenged traditional Western economic dominance and has led to increased cooperation and coordination among these diverse nations. As they continue to grow and develop, the prospects for the BRICS countries are immense. However, they also face numerous challenges, such as income inequality, political instability, and environmental degradation. In this essay, we will explore the potential opportunities and obstacles that the BRICS countries face in their path towards sustainable development and economic prosperity